2021
DOI: 10.1016/j.celrep.2021.109384
|View full text |Cite
|
Sign up to set email alerts
|

EGY3 mediates chloroplastic ROS homeostasis and promotes retrograde signaling in response to salt stress in Arabidopsis

Abstract: EGY3 mediates chloroplastic ROS homeostasis and promotes retrograde signaling in response to salt stress in Arabidopsis Graphical abstract Highlights d EGY3 enhances plant tolerance to salt stress d EGY3 mediates chloroplastic ROS homeostasis and retrograde signaling d EGY3 interacts with and stabilizes Cu/Zn-SOD2 under salt stress

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 105 publications
2
31
0
Order By: Relevance
“…This result correlates with hydrogen peroxide concentrations, which are lower in egy3 mutant exposed to analyzed stress conditions. These findings agree with the previous findings concerning the EGY3 role in the salt-stress response (Zhuang et al, 2021). The exposition to high-temperature stress, however, did not cause any statistically significant differences in the abundance of CSD2 protein in egy3 mutants; however, the lower, than in WT plants, the concentration of hydrogen peroxide was observed.…”
Section: Locussupporting
confidence: 92%
See 2 more Smart Citations
“…This result correlates with hydrogen peroxide concentrations, which are lower in egy3 mutant exposed to analyzed stress conditions. These findings agree with the previous findings concerning the EGY3 role in the salt-stress response (Zhuang et al, 2021). The exposition to high-temperature stress, however, did not cause any statistically significant differences in the abundance of CSD2 protein in egy3 mutants; however, the lower, than in WT plants, the concentration of hydrogen peroxide was observed.…”
Section: Locussupporting
confidence: 92%
“…It was shown that the EGY3 pseudoprotease participates in the stabilization of a chloroplastic copper/zinc superoxide dismutase (CSD2) in response to salt stress (Zhuang et al, 2021). Our results indicate that in response to high light stress, the presence of EGY3 pseudoprotease reassures a higher abundance of CSD2.…”
Section: Locusmentioning
confidence: 61%
See 1 more Smart Citation
“…According to our data, Os03g0729000 was significantly up-regulated after drought stress. Furthermore, we inferred by NR annotation that Os03g0729000 was likely to be zinc metalloprotease EGY3, which can promote the stability of chloroplast copper/zinc superoxide dismutase and improve stress resistance when plants are stressed [ 33 ]. In addition, we predicted that 28 lncRNAs could target Os03g0729000 (EGY3), and all of them were up-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Several abiotic stresses enhance ROS accumulation in the chloroplast, a major site of ROS production 22 , 41 , 42 . Recently, ROS was proposed to act as a retrograde signal to influence plant responses to abiotic stresses, particularly for plant tolerance to salt stress 43 . This raises an exciting question of whether chloroplastic ROS could act as a retrograde signal under Fe deficiency to regulate the expression of nuclear PRGs.…”
Section: Discussionmentioning
confidence: 99%